On the Diophantine equation x2+3a41b = yn - Alan, Murat; Zengin, Ugur (SPRINGER, 2020)
In this paper we find all positive integer solutions (x, y, n, a, b) of the equation in the title for non negative integers a and b under the condition that the integers x and y are relatively prime and n >= 3.
Keywords: Diophantine equations; Ramanujan-Nagell equations; Primitive divisor theorem; X(2)+2(A); Mathematics